RUANG LINGKUP MANAJEMEN PERKANTORAN DALAM PERSPEKTIF AL-QUR’AN - Mirda, Merda Rahayu; Vinna, Syevinna Alifia Dinta; Nasrun, Nasrun Harahap (As-Sulthan Journal of Education, 2025)
The Scope of the Role of Office Management is all aspects related to office management to create quality performance. The role of Office Management can help improve office efficiency, effectiveness and productivity and achieve organizational goals. The purpose of this study is to explore the verses of the Qur'an about the Scope of the Role of Office Management from the Perspective of the Qur'an. This type of research is qualitative research using literature review. This study uses a thematic approach, combining several verses of the Qur'an that discuss the Scope of the Role of Office Management in improving work efficiency and effectiveness. The primary data sources in this study are the Qur'an, Tafsir Ibu Katsir and Tafsir Al-Munir. While secondary data is taken from books, journal articles, websites related to the discussion. The data analysis technique uses content analysis. The results of the study indicate that the Scope of the Role of Office Management from the Perspective of the Qur'an are: (1) Mature Planning (Takhtit); (2) Structured Organization (Thanzim); (3) Implementation (Tatbiq) and (4) Supervision (Riqabah). The conclusion of this study emphasizes the importance of taking on the task of increasing the productivity and quality of the educational environment